Primary isolated extranodal NK/T-cell lymphoma of the orbit: A case report and diagnostic dilemma - Bhanvadia, Viral M; Kathiara, Ravija (Indian Journal of Case Reports, 2024)
Natural killer T-cell lymphoma (NKTL) is associated with Epstein-Barr virus, a highly malignant tumor that typically arises in the nose and/or paranasal sinuses isolated orbital involvement by NKTL is extremely rare. Herein, we report a case of primary orbital NKTL in a young female patient. A 32-year-old female presented with gradually increasing painful swelling of the right eye. On examination, abaxial proptosis, inferolateral displacement of the eyeball, restricted extraocular muscle movement, and solid mass in the subconjunctival fornix and superior quadrant. The rest of the ocular and systemic examination was unremarkable. Magnetic resonance imaging with contrast of the orbit shows a lobulated mass lesion 35×30×18 mm involving the medial aspect of the right orbit extraconal and superior intraconal space extending up to the preseptal region. Informed consent and biopsy were done and sent for histopathology examination. Histopathological examination shows the spectrum of atypical lymphoid cells, indented or cleaved nuclei and pale to clear cytoplasm, few histiocytes, giant cells, and apoptotic body. To rule out lymphoma, immunohistochemistry (IHC) was advised. On IHC, tumor cells were positive for CD3, D56, CD4 focally, CD7, Ki-67–90% and negative for CD20, CD2, Tdt, PAX5, CD34, CD5, Cd8 leading to a diagnosis of extranodal NKTL of the orbit. To the best of our knowledge, around 20 cases of isolated orbital extranodal NKTL were reported in the literature review. Polymorphic lymphoid cell in a young patient often mimics the inflammatory conditions of orbit. The rarity of this tumor and inflammatory signs make it challenging to identify these tumors early.